Parental Guidance and Its Implications on the Attitudes of Children Aged 7-8 Years of Using Gadgets : Study in Children in Two Large Cities, East Jakarta and Makassar - Nurjannah Nurjannah (SEA-CECCEP, 2020)
This study aims to: (1) Obtain information about guidance given by parents to children aged 7-8 years in using gadgets; (2) Obtain opinions, feelings, and desires of children aged 7-8 years in using gadgets; (3) Discover the difference between parental guidance for children aged 7-8 years in using gadgets in East Jakarta and Makassar. (4) Discover the relationship between parental guidance and attitudes of children aged 7-8 years in using gadgets. This study used a quantitative approach with descriptive analysis techniques, correlation analysis and comparative analysis. The scope of the study included children aged 7-8 years in grade 2 elementary school and their parents who lived in 2 big cities, namely East Jakarta and Makassar. The sampling technique used was cluster random sampling (group random). Random groups were conducted by randomly assigning public elementary schools in East Jakarta and Makassar City. The results showed:(1) Parental guidance as a pattern of interaction between parents and children showed that the condition of parents had sufficient intensity in providing information about the use of appropriate gadgets, helping children identify and distinguish appropriate behavior in using gadgets , providing guidance and rules for children, and applying discipline in the use of gadgets, yet parents are still low on inviting children to communicate about rules and rewards in using gadgets; (2) The attitude of children aged 7-8 years to the use of gadgets shows that children tend to be positive to ask more knowledgeable people, to find out through the internet, to distinguish types of gadgets, to focus on frequency and duration of use of gadgets, yet tend to be negative in opening available applications, explaining the way how to use of gadgets, exemplifying the use of gadgets, changing gadget functions and anxiety when there are no gadgets; (3) There is a difference between the guidance of parents of East Jakarta and Makassar cities; (4) There is no difference between the children’s attitudes of East Jakarta and Makassar city towards the use of gadgets, which showed the same things in the 2 cities.